The New York State Police cordoned off the State... - Civil Service Employees Association (CSEA) (Civil Service Employees Association, Inc. (CSEA), American Federation of State, County, and Municipal Employees (AFSCME) Local 1000 Records, 2000)
The New York State Police cordoned off the State Capitol during Governor George E. Pataki's State of the State speech as 20,000 Civil Service Employees Association (CSEA) and PEF members protested stalled contract talks at the Empire State Plaza.